IMPROVING EDUCATION AND DETERMINING THE NUTRITIONAL STATUS OF TODDLERS IN REALIZING NUTRITION-CONSCIOUS FAMILIES IN BANYUWANGI USING R-SHINY - Chamidah, Nur; Kurniawan, Ardi; Saifudin, Toha; Sa'idah, Andini; Widyawati, Ayu; Fajrina, Sofia (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
Stunting is a condition where a child's development and growth is disturbed, which has long-term impacts, including the potential for impaired brain development due to insufficient cognitive development and a greater risk of developing chronic diseases such as diabetes, hypertension, obesity, cancer, and so on. One effort to reduce stunting rates is to increase knowledge of nutrition awareness in the family. UNAIR Statistics Study Program, participates in efforts to reduce stunting rates with community service activities (Pengmas), in the form of outreach activities regarding basic and practical knowledge in the form of workshops and training activities using R-Shiny based WEB and Android to determine the nutritional status of toddlers which can used anywhere and anytime. This community service activity was carried out in the working area of "‹"‹the Tampo Community Health Center, Banyuwangi, East Java, involving 62 female cadre representatives from 31 local posyandu. The results of this community service activity can increase knowledge regarding education and nutrition knowledge for toddlers in the context of achieving nutrition-aware families. This is proven by the results of statistical analysis of pre-test and post-test scores which conclude that there is an increase in scores from pre-test to post-test with a significance level of 5%. Based on the results of the feedback questionnaire given to participants, the posyandu cadre mother felt very satisfied with an average score of 86, gained useful knowledge, and made it easier for posyandu cadres to find out the nutritional status of toddlers.